Sosialisasi Bahaya JUDOL (Judi Online) Dalam Perspektif Ekonomi di SMKN 2 Sungailiat-Bangka - Sihombing, Septiana; Sahputri, Rindi Ardika Melsalasa; Njoman, Muhammad Galy; Rini, Lamia Eva (Politeknik Negeri Batam, 2025)
Online games are currently an alternative to gambling online in secret and have a dangerous impact on the economy and mental health of its players. The problem that occurs, with very easy digital access in various groups including teenagers, teenagers are unable to distinguish and identify online gambling with regular online games, coupled with fairly low digital literacy. This problem also occurs among teenagers at the vocational school level in Sungailiat which shows low knowledge about online gambling. For this reason, it is important to make community service efforts by conducting socialization to educate students about online gambling and its dangers from an economic perspective. The method used to carry out this community service is in the form of socialization starting from socialization preparation, program implementation to program evaluation which is carried out pre-test, post-test and qualitatively. The results show an increase in student knowledge about online gambling and its dangers to the economy and a decrease in student interest in carrying out activities related to online gambling.